METHOD OF ASSESSMENT OF FORMATIVE EQUIPMENT VIABROACOUSTICAL PARAMETERS: Array - , В. І., П. А. (Municipal economy of cities. Series: «Economy science», 2018)
Noise is one of shkіdlivih factors in a vibration middle-aged; yaks cause not only professional apprehension, but also the trauma of virobnitstv. Naybіlshu Іntensivnіst vіbroakustichnogo colivannu є possession on the surface of the great rosmirіv. Before them, you should get into a different form for possession, when you have concrete mixes for a sound of 10 - 20 dB, but for standard values. Reducing noise in a new story is the most radical method and the main one. Ties is a method of tackling the zip with the reduced noise characteristics of the voriforming aggregates and those of the technologic possession in that which can be achieved in the design of new types of machines that are mechanically equipped, and the wrists of the wise men who have been drawn by the wise men and women, who have been trained by the wise men and women, and who are the masters of the master, who are the master of the master, and who are the master of the wise men and women who are equipped with the new characteristics of the machines and machines that are equipped by the master, and which are kept by the ladies. The subject of a Danish doslіdzhen sound energy, yak vipromіnyuvatsya vіbroploshchadkami (and exactly mealtime forms) at the same time with concrete concrete at virobnittv flat zalіzobetonnyh virobіv. The reduction of acoustically en erg, yaks generator form is followed by the construction of the curved cultivation of the piddon sheath and the most important elements of metal constructions. Ties nobles are to be seen in the dynamic characteristics of the system, the frequencies of the frequencies and the common forms of constructive elements, especially in them, they may find their best on the surface. Analyzing what's happening to the shumovіbrozakhistu, showing that we can find out who we can for half the brain of the best of the operators in the form of possession. The authors of the algorithm for rozrahunk ochenkuvikh rіvnіv sound plating pіddonu form in the near field of direct sound that її harmonic, yak poligaє in the so-called "vіdbudovi" sozolnyh colivan that їх harmonic. Otrimanі results and allow them to determine the frequency and power of the skin in the frame of the primacy of life at the construction of such resonance, as well as reduce the size of the mobile radio campaign on the issue, for example. The method has been broken down to allow design organizations and factories to win plants to meet the requirements of concrete and vibration and to get more efficiently, from the point of view of their workmanship, possession. Won's permission for virishuvati is caused by the reduced noise of the yak of a modern wedge form, as well as new formulas, which are re-designed, re-designed by the instructor for experimental purposes. Keywords: sound, vibration, frequency, vibroplane, sound power, sound absorption, stiffness of structures.